Integrating Zero Trust Architecture with Service Mesh for Enhanced Cloud Security in DevOps Workflows - Dindigala, Raju; Dandyala, Sai Surya Mounika (International Journal of Computer and Information System (IJCIS), 2024)
The increasing adoption of cloud-native architectures and DevOps workflows has revolutionized software development and deployment but has also introduced complex security challenges. To address these challenges, Zero Trust Architecture (ZTA) has emerged as a critical paradigm, emphasizing the principle of "never trust, always verify." When combined with service mesh technology, which provides granular control over service-to-service communication, ZTA can create a robust security framework for cloud environments.This paper builds on the foundational work of Sandeep Pochu, Sai Rama Krishna Nersu, and Srikanth Reddy Kathram, as outlined in their paper "Enhancing Cloud Security with Automated Service Mesh Implementations in DevOps Pipelines." Their research highlights the value of automated service mesh deployments in securing cloud-native environments within DevOps pipelines. Extending this work, we explore the integration of ZTA principles into service mesh implementations to further enhance security.We propose a framework that leverages service mesh telemetry, mutual TLS (mTLS), and advanced access control mechanisms to enforce ZTA principles at the microservices level. By embedding Zero Trust policies directly into the communication fabric of cloud-native applications, this approach ensures end-to-end security, minimizes attack surfaces, and reduces the risk of lateral movement by attackers. Additionally, we examine how this integration can be automated within DevOps workflows, ensuring that security configurations remain consistent and scalable in dynamic cloud environments. Through case studies and experimental evaluations, we demonstrate the effectiveness of this framework in detecting and mitigating threats while maintaining the agility of DevOps processes. The results show significant improvements in access control, anomaly detection, and response times, underscoring the potential of combining ZTA with service mesh technology. This paper aims to provide actionable insights for organizations seeking to enhance cloud security by integrating these cutting-edge technologies.